2019
DOI: 10.1039/c8cy02546k
|View full text |Cite
|
Sign up to set email alerts
|

Cu@ZIF-8 derived inverse ZnO/Cu catalyst with sub-5 nm ZnO for efficient CO2 hydrogenation to methanol

Abstract: Cu@ZIF-8 derived inverse ZnO/Cu with sub-5 nm ZnO acts as an efficient catalyst for CO2 hydrogenation to methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…The results found that 10 wt% CuZn/rGO catalyst exhibited a good activity for the CO 2 hydrogenation, achieving 26 % CO 2 conversion, methanol selectivity of 51%, and 424 ± 18 mg methanol at 250°C under 15 bar after 5 h on a stream (Deerattrakul et al, 2016). With MOF as a support or component of catalyst, very high methanol selectivity (up to 100%) was reported (Rungtaweevoranit et al, 2016;An et al, 2017;Hu et al, 2019). Still, its application suffers from serious challenges that are undesirable for industrial applications-low conversion and instability at high temperatures.…”
Section: Non-metal Oxide Supportsmentioning
confidence: 95%
“…The results found that 10 wt% CuZn/rGO catalyst exhibited a good activity for the CO 2 hydrogenation, achieving 26 % CO 2 conversion, methanol selectivity of 51%, and 424 ± 18 mg methanol at 250°C under 15 bar after 5 h on a stream (Deerattrakul et al, 2016). With MOF as a support or component of catalyst, very high methanol selectivity (up to 100%) was reported (Rungtaweevoranit et al, 2016;An et al, 2017;Hu et al, 2019). Still, its application suffers from serious challenges that are undesirable for industrial applications-low conversion and instability at high temperatures.…”
Section: Non-metal Oxide Supportsmentioning
confidence: 95%
“…It has been documented that copper-based catalysts are highly active in CO2 hydrogenation to methanol [11][12][13][14] , which have been widely used in this process of CO2 hydrogenation owing to its high catalytic performance and the moderate price. Typically, Cu species always combine with metal oxides (such as ZnO 10,[15][16][17][18][19] , ZrO2 [6][7][8][20][21][22][23][24][25] , and CeO2 [26][27][28][29] ) making more active sites for better performance towards methanol synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, Cu–ZnO and Fe 3 O 4 are active for rWGSR 43 and Cu–ZnO interfaces are also responsible for methanol production. 44 As for the production of higher carbon products, iron carbide has been regarded as the active site for C–O dissociation and C–C coupling while the Cu site for C–O non-dissociative activation. 45,46 The active Cu–Fe x C interfaces are able to produce C 2+ alcohols.…”
Section: Resultsmentioning
confidence: 99%